Study of Atmospheric Discharge Effects in Distribution Networks with a Novel Residential Buildings Protection Approach - Meisam Karami; Yazdan Ashgevari (Advances in Engineering and Intelligence Systems)
Lightning-induced overvoltage poses a significant threat to electrical equipment and building structures. This study aims to comprehensively investigate lightning overvoltage in low voltage distribution lines under different scenarios, including lightning strikes to the ground, direct discharge through distribution lines, and direct discharge through antennas. The MATLAB simulation program is employed for conducting simulations, and the results reveal noteworthy findings. Specifically, the analysis demonstrates that the magnitude of overvoltage resulting from lightning discharge through distribution lines and antennas surpasses that observed from discharge to the ground. Furthermore, the study explores lightning strikes occurring in the vicinity of buildings, leading to a rise in ground potential and indicating the potential reverse flow of lightning current from the ground system towards the building. By shedding light on these phenomena, this research contributes to a deeper understanding of lightning overvoltage behavior and aids in the development of effective mitigation strategies for safeguarding electrical systems and building infrastructure.